2022
DOI: 10.3390/nu14030508
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hydrogen Mitigates Performance Decrement during Repeated Sprints in Professional Soccer Players

Abstract: Hydrogen-rich water (HRW) supplementation has been shown to have an antifatigue effect across different modes of exercise. However, its effect on repeated sprint performance is unknown. The aim of this study was to assess the effect of pre-exercise HRW consumption on repeated sprint performance, lactate, and perceptual responses using a repeated sprint protocol. This randomized, double blinded, placebo controlled, crossover study included 16 professional, male soccer players aged 18.8 ± 1.2 years. Athletes per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Hence, we suggest that 2 weeks of daily H 2 inhalation resulted in a clinically relevant improvement in physical function in our cohort of acute post-COVID-19 patients. From an improved physical fitness standpoint, the antifatigue effect of H 2 demonstrated in the present study has already been documented in other studies examining different modes of exercise in a healthy population [ 26 , 27 ], well-trained athletes [ 25 , 45 , 59 ], and animal models [ 24 ]. The antifatigue effect of H 2 supplementation was explained by its ability to stimulate oxidative metabolism, reduce oxidative stress, adjust the cellular redox environment and improve immune function.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Hence, we suggest that 2 weeks of daily H 2 inhalation resulted in a clinically relevant improvement in physical function in our cohort of acute post-COVID-19 patients. From an improved physical fitness standpoint, the antifatigue effect of H 2 demonstrated in the present study has already been documented in other studies examining different modes of exercise in a healthy population [ 26 , 27 ], well-trained athletes [ 25 , 45 , 59 ], and animal models [ 24 ]. The antifatigue effect of H 2 supplementation was explained by its ability to stimulate oxidative metabolism, reduce oxidative stress, adjust the cellular redox environment and improve immune function.…”
Section: Discussionsupporting
confidence: 79%
“…In general, rehabilitation after COVID-19 ranged from 5 days to 6 months [ 44 ]. In sports medicine, the duration of H 2 administration prior to exercise ranged from 30 min to 4 weeks [ 45 ]. Therefore, we chose a 14-day H 2 /placebo intervention as a compromise to keep the duration long enough to reveal a detectable effect on physical and respiratory outcomes, yet acceptably short for study compliance.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent study reported that the ingestion of high concentrations of H 2 in saturated water (approximately 5.0 ppm) attenuated the reduction in systemic antioxidant capacity after three consecutive days of sprint cycling exercise ( Dobashi et al, 2020 ). Moreover, H 2 concentrations of approximately 1.0 ppm improved muscular performance in a previous study ( Aoki et al, 2012 ; Botek et al, 2021 , 2022 ). Since there is no clearly defined dose-response curve of H 2 to induce physiological changes ( Ostojic, 2015 ), it is uncertain whether an H 2 concentration of 0.3 ppm is enough to improve various exercise performances and redox responses.…”
Section: Discussionmentioning
confidence: 48%
“…Our previous studies demonstrated that H 2 attenuated the intensive exercise-induced elevation in oxidative damage or the reduction in antioxidant capacity in humans ( Koyama et al, 2008 ; Dobashi et al, 2020 ; Shibayama et al, 2020 ) and thoroughbred horses ( Yamazaki et al, 2015 ). Moreover, H 2 -rich water improved muscle fatigue ( Aoki et al, 2012 ; Botek et al, 2021 , 2022 ) and attenuated an increase in blood lactate concentrations during exercise ( Drid et al, 2016 ; Botek et al, 2019 , 2021 ; Mikami et al, 2019 ), as well as inflammatory responses ( Ara et al, 2018 ; Nogueira et al, 2018 , 2021 ). Furthermore, a recent study reported that AEW ingestion improved energy expenditure during submaximal endurance cycling in a heated environment ( Ito et al, 2020 ).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, dissolving hydrogen in haemodialysis solutions can decrease plasma concentrations of pro-inflammatory factors in haemodialysis patients [ 11 ]. Intake of hydrogenated water prior to exercise was also reported to reduce fatigue [ 12 ]. Although numerous studies have illustrated the beneficial effects of hydrogenated water in human health, the instability of its redox status and difficulties in quantifying the levels of dissolved hydrogen in water have limited its application.…”
Section: Introductionmentioning
confidence: 99%